Decoding allelic diversity, transcript variants and transcriptional complexity of CENH3 gene in Brassica oleracea var. botrytis. - Raipuria, Ritesh Kumar; Watts, Anshul; Sharma, Brij Bihari; Watts, Archana; Bhattacharya, Ramcharan (Protoplasma, 2023)
Histone proteins play a critical role in the primary organization of nucleosomes, which is the fundamental unit of chromatin. Among the five types of the histones, histone H3 has multiple variants, and the number differs among the species. Amongst histone H3 variants, centromeric histone H3 (CENH3) is crucial for centromere identification and proper chromosomal segregation during cell division. In the present study, we have identified 17 putative histone H3 genes of Brassica oleracea. Furthermore, we have done a detailed characterization of the CENH3 gene of B. oleracea. We showed that a single CENH3 gene exhibits allelic diversity with at least two alleles and alternative splicing pattern. Also, we have identified a CENH3 gene–specific co-dominant cleaved amplified polymorphic sequence marker SNP34(A/C) to distinguish CENH3 alleles and follow their expression in leaf and flower tissues. The gene structure analysis of the CENH3 gene revealed the conserved 5′–CAGCAG–3′ sequence at the intron 3–exon 4 junction in B. oleracea, which serves as an alternative splicing site with one-codon (alanine) addition/deletion. However, this one-codon alternative splicing feature is not conserved in the CENH3 genes of wild allied Brassica species. Our finding suggests that transcriptional complexity and alternative splicing might play a key role in the transcriptional regulation and function of the CENH3 gene in B. oleracea. Altogether, data generated from the present study can serve as a primary information resource and can be used to engineer CENH3 gene towards developing haploid inducer lines in B. oleracea.